Assessment and Risk Classification Issues of Youth Problem Gambling - Dodig, Dora (2011)
Rates of adolescent problem gambling are usually three times higher comparing to adults. It is unclear whether usual screening instruments can accurately assess problem gamblers because they rely on adult definition of problem, use dichotomous response formats, are based on relatively low cut-off scores and include questions that adolescent may not understand. The main purpose of this presentation is to compare gambling addiction risk classification using two most common screening instruments: SOGS-RA and DSM-IV-J. Both instruments were modified in response format into continuous variables, which improved their sensitivity, preserving high reliability. Research was conducted on a sample of 261 high-school students in the City of Zagreb. Results indicate a larger percentage of risk and problem gamblers, and interpretable two-factor solutions for both instruments. Discussion will focus on concordance among these two instruments and the effects modification has on assessing risk for gambling addiction, with presentation of new trends in assessments.